2021
DOI: 10.1016/j.amsu.2021.103120
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cervical spine surgery for treatment of secondary dysphagia associated with cervical myelopathy in patient with Forestier's disease

Abstract: Introduction and importance: Forestier's disease, also known as a vertebral ankylosing hyperostosis or Diffuse Idiopathic Skeletal Hyperostosis (DISH), is a non-inflammatory enthesopathy that affects primarily elderly males and ossifies the anterolateral spine while sparing the intervertebral discs and joint spaces, especially at the cervical spine. Forestier's disease has resulted in the growth of large anterior cervical osteophytes that may compress the pharyngoesophageal region, producing dysph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…DISH is a systemic disease characterized by excessive calcification of the anterior spinal body, primarily at the T8-T10 level [3] . The etiology is still unclear; the prevalence of DISH in the Asian population ranges between 10 and 25% [5] . The majority of patients are asymptomatic, although compression of the anterior component of the cervical spine can cause dysphagia, recurrent pneumonia, and airway obstruction [2] , [6] , [7] .…”
Section: Clinical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DISH is a systemic disease characterized by excessive calcification of the anterior spinal body, primarily at the T8-T10 level [3] . The etiology is still unclear; the prevalence of DISH in the Asian population ranges between 10 and 25% [5] . The majority of patients are asymptomatic, although compression of the anterior component of the cervical spine can cause dysphagia, recurrent pneumonia, and airway obstruction [2] , [6] , [7] .…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Reformation of an osteophyte has been found to occur at a rate of 1 mm/year; however, recurrence of symptoms after surgical resection occurs slowly and in very few patients [10] . Apart from surgical resection, additional fusion, NSAIDs, bisphosphonate, indomethacin and radiotherapy have been used to reduce the risk of recurrence, but there are no precise guidelines for prophylaxis to prevent recurrence [5] , [11] .…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Similar to axSpA, also Achilles tendon and plantar fascia are affected [2]. While in daily practice arthritis and enthesitis are more common in axSpA than in DISH, studies with small numbers of patients demonstrated the presence of inflammatory signal on power Doppler but also presence of erosions also in DISH-associated enthesopathies [33]. In addition, typical extra-musculoskeletal manifestations of axSpA, such as uveitis, psoriasis, and inflammatory bowel disease are not found in patients diagnosed with DISH.…”
Section: Similarities and Differences In Clinical Featuresmentioning
confidence: 99%